Documenting verbal practices: Pilagá text collection - Vidal, Alejandra Silvia (2021)
The Pilagá collection of texts is the result of several projects which have provided the means to record and build an archive of linguistically annotated and representative Pilagá language textual corpus. This is the first systematic initiative entailing the construction of a text archive in the original language, translated into Spanish and English. The texts represent a diverse sample of Pilagá narrative involving around twenty speakers from all the Pilagá communities in the center-west of the province of Formosa, Argentina. Pilagá (belonging to the Guaycuruan family) is an endangered language spoken by less than 5,000 people of different age groups. This article addresses the organization and classification of the texts included in the collection, with special attention to the narratives and descriptions. Some methodological issues are presented in connection with text elicitation and cataloguing, with discussion of some features such as subtypes and themes. These texts not only represent the tradition and social memories of a hunter-gatherer society, but also reveal the symbolic construction of the moral landscape, beliefs, spiritual connection to the universe, and their convergence with aesthetic expressions of verbal art.